Initial impact and operational responses to the COVID-19 pandemic by American Radiation Oncology practices - Wakefield, Daniel V.; Sanders, Tim; Wilson, Emily; Hubler, Adam; DeWeese, Theodore; Smith, Benjamin D.; Slotman, Berend J.; Sarria, Gustavo R.; Eichler, Thomas; Schwartz, David L. (International journal of radiation oncology, biology, physics, 2020)
Purpose - In February 2020, the COVID-19 pandemic reached the United States. The impact of the pandemic on the US radiation oncology field remains unknown. The American Society for Radiation Oncology surveyed US radiation oncology practice leaders to gauge initial impact and immediate operational responses to the pandemic. - Methods and Materials - From April 16 to April 30, 2020, the American Society for Radiation Oncology surveyed US radiation oncology practice leaders by email to gauge initial impact and immediate operational responses to the COVID-19 pandemic. - Results - Two hundred twenty-two (43%) of 517 leaders responded from community and academic practices (62% and 34%, respectively), hospital-based and free-standing centers (69% and 29%), and metro and rural locations (88% and 12%). Practices reported treating an average of 1086 patients per year in 2019 (range, 0-7900) with an average daily treatment volume of 70 patients (range, 5-400). All practices reported uninterrupted operation. On average, practices were treating 68% of their typical volume (range, 10%-95%), with 92% implementing planned treatment postponement for lower risk patients. An estimated revenue decrease of 20% or more was experienced by 71% of practices. Confirmed COVID-19 patient cases were treated by 39% of practices. Seventy percent experienced staff shortages. Almost all (98%) practices implemented formal operational procedures to protect patients and staff, although personal protective equipment/infection control supply shortages were reported by 78% of practices. Seventy-four percent used telemedicine for virtual follow-up surveillance, and 15% leveraged telemedicine for on-treatment assessment. - Conclusions - The clinical and financial impacts of the COVID-19 pandemic on US radiation oncology were deep and broad. Despite reported shortages in personal protective equipment, declines in revenue, and reduced patient volumes, practices adapted quickly by refining standard processes of care, implementing recommended safety measures, and employing telemedicine to facilitate treatment continuity. Patients with higher risk disease experienced uninterrupted access to care. We plan to continue regular surveying across the lifespan of the pandemic to document the geographic and temporal impact of COVID-19 on the field and its patients.
Gesehen am 08.08.2025